2015
DOI: 10.1159/000369471
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Competence in Simulated Flexible Bronchoscopy Using Motion Analysis

Abstract: Background: Flexible bronchoscopy should be performed with a correct posture and a straight scope to optimize bronchoscopy performance and at the same time minimize the risk of work-related injuries and endoscope damage. Objectives: We aimed to test whether an automatic motion analysis system could be used to explore if there is a correlation in scope movements and the operator's level of experience. Our hypothesis was that experienced bronchoscopists move less and keep the flexible scope straighter than less-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
2
10
0
1
Order By: Relevance
“…The remaining studies [13, 19-23, 27, 28, 32, 34, 37, 38] either tested various training methods [20,27,28,32,34,37,38] , simulators [21][22][23]28] or a new approach to skills assessment [13,19] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies [13, 19-23, 27, 28, 32, 34, 37, 38] either tested various training methods [20,27,28,32,34,37,38] , simulators [21][22][23]28] or a new approach to skills assessment [13,19] .…”
Section: Resultsmentioning
confidence: 99%
“…One study used alternative measurements to assess the learners' skills [19] . An additional study explored the possibility of using a motion sensor to assess the skills of an operator [13] .…”
Section: Flexible Bronchoscopymentioning
confidence: 99%
“…Three studies explored the possibility of using the MK as a tool for skills learning in bronchoscopy and colonoscopy by means of simulation [50,51,108].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were aimed at comparing the performance of the MK with respect to a mouse [45,46]; one compared the performance of the LMC to that of a mouse [47]; and two studies compared different COTS devices [48,49]. Seven studies had the aim of performing construct [50][51][52] or concurrent validation of the devices [53][54][55][56].…”
Section: User Testingmentioning
confidence: 99%
“…Several reports have since shown that virtual reality simulation can be an effective teaching tool, although superiority over other simulation models has not been proven [11]. In the latest issue of Respiration , Colella et al [12] go one step further by evaluating motion analysis of the bronchoscopist during a simulated flexible bronchoscopy. The authors state that only small movements in the bronchoscopist's left hand are necessary for adequate navigation through the patient's airways.…”
mentioning
confidence: 99%